2013
DOI: 10.1007/s00125-013-3031-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in KCNJ11 are associated with the development of autosomal dominant, early-onset type 2 diabetes

Abstract: Aims/hypothesis More than 90% of Chinese familial early-onset type 2 diabetes mellitus is genetically unexplained. To investigate the molecular aetiology, we identified and characterised whether mutations in the KCNJ11 gene are responsible for these families. Methods KCNJ11 mutations were screened for 96 familial early-onset type 2 diabetic probands and their families. Functional significance of the identified mutations was confirmed by physiological analysis, molecular modelling and population survey. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…For example, methylation of one locus in the KCNJ11 gene was significantly higher in the MetS group than in the T2D group and was tending towards significance compared to the control group. Genetic defects in the KCNJ11 gene have been previously associated with an increased risk of diabetic disorders and heart failure, by inducing changes in the heart's response to stress[34,35]. In line with these reports, we could speculate that the elevated levels of DNA methylation in the MetS patient group for this KCNJ11 CpG locus may mimic the genetic defects in the KCNJ11 gene.…”
Section: Discussionsupporting
confidence: 70%
“…For example, methylation of one locus in the KCNJ11 gene was significantly higher in the MetS group than in the T2D group and was tending towards significance compared to the control group. Genetic defects in the KCNJ11 gene have been previously associated with an increased risk of diabetic disorders and heart failure, by inducing changes in the heart's response to stress[34,35]. In line with these reports, we could speculate that the elevated levels of DNA methylation in the MetS patient group for this KCNJ11 CpG locus may mimic the genetic defects in the KCNJ11 gene.…”
Section: Discussionsupporting
confidence: 70%
“…Specifically, HNF1α/MODY3 and KCNJ11/MODY13 were the two most frequent polymorphisms, indicating that these two genes seem to be the most possible common MODY genes identified in the Chinese population so far. 6,19,20 It is of note that most of the polymorphisms detected in the present study have been reported to be associated with T2D. The I27L polymorphism is associated with insulin resistance 21 and both the I27L and S486N variations of HNF1α have been associated with multiple cardiovascular risk phenotypes in the general population of European Americans.…”
Section: Discussionsupporting
confidence: 53%
“…Although no mutations were identified in the patients, different polymorphisms were found, and those polymorphisms affected only five MODY genes: HNF1α /MODY3, CEL/ MODY8, PAX4 /MODY9, ABCC8 /MODY12, and KCNJ11 /MODY13. Specifically, HNF1α /MODY3 and KCNJ11 /MODY13 were the two most frequent polymorphisms, indicating that these two genes seem to be the most possible common MODY genes identified in the Chinese population so far …”
Section: Discussionmentioning
confidence: 94%
“…They emphasize mutation screening, at least of INS , for Japanese patients diagnosed as autoantibody negative at <5 years of age. We further reported that not only NDM but also early‐ and adult‐onset diabetes might be caused by KCNJ11 mutation . All of these data taken together suggest that onset of monogenic NDM is not limited to the first 6 months of life, and that, as a result of the causal gene mutations, diabetes could occur at any time of life.…”
Section: Prevalence Of Monogenic Diabetesmentioning
confidence: 53%